2007
DOI: 10.1097/01.brs.0000259206.38946.cb
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopic Video to Identify Aberrant Lumbar Motion

Abstract: DFV was useful for discriminating between individuals with and without LBP based on kinematic parameters. Disruptions in how the motion occurred during midrange motions were more diagnostic for LBP than range of motion variables. Cross validation of the model is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 53 publications
2
54
1
1
Order By: Relevance
“…This research confirms and extends the results of previous studies [8,24,29] that found abnormalities of shared intervertebral motion to be consistent with having CNSLBP and suggests possible mechanisms for this. It also suggests routes for improved understanding of the role of disc degeneration in common back pain in which degeneration may be considered a pain source when it is associated with uneven motion sharing and end-plate signal change.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…This research confirms and extends the results of previous studies [8,24,29] that found abnormalities of shared intervertebral motion to be consistent with having CNSLBP and suggests possible mechanisms for this. It also suggests routes for improved understanding of the role of disc degeneration in common back pain in which degeneration may be considered a pain source when it is associated with uneven motion sharing and end-plate signal change.…”
Section: Resultssupporting
confidence: 91%
“…Although its measurement has been generally confined to cadaveric studies, the advancing sophistication of quantitative fluoroscopic systems (QF) is beginning to provide a surrogate in vivo measure in the form of slope of the intervertebral rotation-time curve (also known as the attainment rate) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated t-tests for continuous variables. Continuous variables with p value \ 0.20 were retained for further analysis [37,38]. The more liberal cutoff values were used to preferentially protect against Type II error at this early state of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional radiographic assessment has some limitations, such as large variation, being based on static postures at extreme ranges of motion and associated large measurement errors [7,[22][23][24][25][26][27]. Therefore, there is a need for tools to assess kinematics in vivo in order to measure the motion characteristics in midrange, where aberrant motion and dysfunction have been postulated to occur, based on neutral zone concept put forth by Panjabi et al [28,29].…”
Section: Introductionmentioning
confidence: 99%